"Słoje", "słoiki" i "słoiczki" kontra "lokalesi", "rodowici" i "slumsy", czyli jak warszawianie postrzegają przyjezdnych i jak przyjezdni postrzegają warszawian = Jars vs lokales, natives and slums - how Warsaw inhabitants perceive incomers and how incomers percive Warsaw inhabitants - Dawidziak-Kładoczna, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the interest is the ongoing Internet debate concerning the relations between the native inhabitants of Warsaw and incomers working in this city. The images of both incomers, often referred to as "słoiki", and native inhabitants of Warsaw, often referred to as "lokales" and "slums", are created thanks to such notions as defining, classifying, wordplaying, wordbuilding and using expressive lexis.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie